EDUCATIONAL POLICY AND NATIONAL SECURITY OF UKRAINE - Полухін, Анатолій Васильович (Science-based technologies, 2019)
The following is considered – world tendencies of development in education and educational policy of the states in conditions of globalization, peculiarities and place of Ukraine’s education in international market of educational services. Taking into account the fact that national security problems are in the focus of the most civilized countries, interstate institutions and public associations today, the content of concepts «the educational policy» and «national security» is analyzed. The following is investigated – education’s role in ensuring defense capacity and security of the state, interrelation of education, educational policy and national security, and also influence of the human capital and its components on national security of Ukraine in context of domestic and international experience. It is shown that one of major factors of the human capital and, as a result, the national security development is not only education quality improvement as such, but first of all, improvement of teaching quality of mathematical and natural-scientific disciplines in general secondary education and higher education systems. In connection with introduction in domestic education the so called «competence based» approach, the essence of such concepts as «knowledge», «ability» and «skills» (which are the basic components of concept «competence») is analyzed. It has been shown, that Ukrainian education is in a crisis condition, particularly with regard to teaching mathematical and natural-scientific disciplines. Some reasons of such a threatening to the national security of the state phenomenon as tangible outflow of Ukrainian citizens to other countries for business or studying have been also analyzed in the context of Ukrainian education policy. Judging by the impressive scale of labor and academic migration of Ukrainians, there is rendering lifeless of not only labor and mobilization resources but also the national gene pool of Ukraine. Some possible ways of addressing these negative phenomena have been considered.